2019
DOI: 10.1177/0844562119856224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Function Focused Care and Physical Activity on Falls in Assisted Living Residents

Abstract: Background There continues to be a belief among nurses, patients, and families that physical activity increases the risk of falling. Purpose The purpose of this study was to test the hypothesis that controlling for age, function, cognition, medication use, gender, comorbidities, and cognition, residents who are exposed to Function Focused Care for Assisted Living (FFC-AL-EIT) and engage in moderate levels of physical activity would not be more likely to fall. Methods This was a secondary data analysis using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Schneider (2017) [30] added that nurses need to be aware of ongoing research regarding vitamin D and provide information about this important vitamin for stroke patients. Also, Resnick et al (2020) [31] concluded that engagement of patients in moderate level physical activity was found to be slightly protective from falling.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider (2017) [30] added that nurses need to be aware of ongoing research regarding vitamin D and provide information about this important vitamin for stroke patients. Also, Resnick et al (2020) [31] concluded that engagement of patients in moderate level physical activity was found to be slightly protective from falling.…”
Section: Discussionmentioning
confidence: 99%
“…A higher percentage of those who were able to stand for 5 seconds with or without an assistive device were found in the complete group. Since the implementation of restorative care could involve a higher level of physical activity, which had been proved to have no association with adverse events [19,33,34], those who were involved, however, might still worry about the higher risk of falling as a consequence, and falling was the main incident among litigation against care facilities in Taiwan [35]. The cognitive status did not show significant differences, indicating that this character may not affect the possibility of staying in the program.…”
Section: Discussionmentioning
confidence: 99%
“…To create focus, the organizers identified 3 areas of clinical relevance to long-term care: (1) functional care and outcomes, (2) psychosocial care and quality of life, and (3) medical care and outcomes. Clinical trials have demonstrated effective approaches to care in these areas, including to increase physical activity, 6,7 decrease falls, 8,9 improve management of behavioral expressions, 10,11 prevent transfers to acute care settings and address goals of care, 12 improve medication management, 13 and enhance infection/viral control. 14,15 However, evidence of efficacy based on randomized controlled trials does not generally change care practices in real world settings.…”
Section: Abstract Pragmatic Trialsmentioning
confidence: 99%